CCAT2 is an oncogenic long non-coding RNA in pancreatic ductal adenocarcinoma - Yi Cai; Xiaomei Li; Peng Shen; Dong Zhang (Biological Research, 2018)
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) is highly aggressive with poor prognosis. Long non-coding RNAs (lncRNAs), a group of non-coding RNAs, play important roles in the progression of PDAC. This study aimed to investigate the potential involvement of lncRNA CCAT2 in PDAC tumorigenesis. Methods Expression of CCAT2 was detected by quantitative real-time PCR (qRT-PCR) in 80 human PDAC tissues and three PDAC cell lines. The effects of CCAT2 silencing in PANC-1 cells on cell proliferation and invasion were studied using MTT assay and transwell assay, respectively. The effect of CCAT2 silencing on tumorigenesis was assessed by PANC-1 xenograft in vivo. Using si-KRAS, the role of KRAS to regulate CCAT2 was evaluated by qRT-PCR and luciferase reporter assay. The involvement of MEK/ERK and PI3K/AKT signaling in CCAT2 regulation was investigated by pathway inhibitors PD98059 and LY294002, respectively. Results CCAT2 was significantly elevated in high-grade PDAC tissues and higher CCAT2 expression was correlated with lower survival rate in PDAC patients. CCAT2 was up-regulated in PDAC cell lines, as compared with normal pancreatic cells. Silencing of CCAT2 inhibited cell proliferation and invasion in PANC-1 cells in vitro, and attenuated tumorigenesis of PANC-1 xenograft in vivo. Furthermore, CCAT2 was regulated by KRAS through MEK/ERK signaling pathway. Conclusions CCAT2 is an oncogenic lncRNA in PDAC likely regulated by the KRAS-MEK/ERK pathway. It could be a potential diagnostic biomarker and therapeutic target for PDAC.